On the 100th anniversary of discovery of epidemic typhus Causative agent – Rickettsia prowazekii (H. Da Rocha Lima, 1916). Whether typhus will return to Russia and Europe? - E. P. Lukin (Журнал инфектологии)
The aim: to confirm the optimal forecast of typhus elimination.The research method: searching and analytical.Results: characteristics of rickettsiosis prowazekii in Russia and neighboring countries after the second world war are presented. The incidence has stopped, the immune population in Russia and Ukraine has decreased from 15,0–23,6% in the 1950–1960s down to 1,4–0,78% at the end of XXth and at the beginning of XXIth c. (until the complete disappearance). The recurrency coefficient (RC) was calculated, and its increase (1:1,000 – 1:1,500 in the first 10–15 years after primary form of the disease up to 1:52 000 after 60 years) further from the time of primary form of the disease was shown. Possibility of the return of the epidemic form is negated, the need for containment of R. prowazekii strains is stressed.